The Crusades and the expansion of Catholic Christendom, 1000-1714 - France, John (Routledge, 2005)
This survey includes illustrations, maps, timelines, further reading guides, and a detailed list of rulers across Europe, and for the first time, chronologically examines the medieval crusades and their impact on European expansion.